Sacred waters
1 online resource
Keywords: "Describing sacred waters and their associated traditions in over thirty countries and across multiple time periods, this book identifies patterns in panhuman hydrolatry. Supplying life's most basic daily need, freshwater sources were most likely the earliest sacred sites, and the first protected and contested resource. Guarded by taboos, rites and supermundane forces, freshwater sources have also been considered thresholds to otherworlds. Often associated with also venerated stones, trees and healing flora, sacred water sources are sites of biocultural diversity. Addressing themes that will shape future water research, this volume examines cultural perceptions of water's sacrality that can be employed to foster resilient human-environmental relationships in the growing water crises of the twenty-first century. The work combines perspectives from anthropology, religious studies, sociology, geography, archaeology, history and folklore"--